Comparative analysis of piRNA sequences, targets and functions in nematodes - Benjamin Pastore; Hannah L. Hertz; Wen Tang (RNA Biology, 2022)
Piwi proteins and Piwi-interacting RNAs (piRNAs) are best known for their roles in suppressing transposons and promoting fertility. Yet piRNA biogenesis and its mechanisms of action differ widely between distantly related species. To better understand the evolution of piRNAs, we characterized the piRNA pathway in C. briggsae, a sibling species of the model organism C. elegans. Our analyses define 25,883 piRNA producing-loci in C. briggsae. piRNA sequences in C. briggsae are extremely divergent from their counterparts in C. elegans, yet both species adopt similar genomic organization that drive piRNA expression. By examining production of Piwi-mediated secondary small RNAs, we identified a set of protein-coding genes that are evolutionarily conserved piRNA targets. In contrast to C. elegans, small RNAs targeting ribosomal RNAs or histone transcripts are not hyper-accumulated in C. briggsae Piwi mutants. Instead, we found that transcripts with few introns are prone to small RNA overamplification. Together our work highlights evolutionary conservation and divergence of the nematode piRNA pathway and provides insights into its role in endogenous gene regulation.